Pengaruh Dewan Komisaris dan Komite Audit pada Kualitas Laporan Keuangan - Nugrahani, Tri Siwi (Akmenika, 2017)
This study aimed to examine the effect of board of directors and the audit committeeon the quality of financial reporting. This research was conducted at the company'slisting on the Stock Exchange in 2011-2014. The sampling method with purposivesampling and data collection methods with observation. This study tested withmultiple regression analysis to test the hypothesis t test with significance of 5 % .Results of hypothesis testing showed that there BOC influence on quality of financialreports is proxied by Return On Investments (ROI) by t test is 3,644 and significance0,000. However, the Audit Committee did not effect the quality of financial statementswith t test is 1.168 and with 0.246 significance. These results indicate that the firsthypothesis was supported, but the second hypothesis is not supported. The higher theBOC role in the company, the higher the Quality of Financial Statements, but if therole of the Audit Committee of the higher will not improve the quality of financialstatements (proxied by ROI). Based on F test amounted to 7.538 with significance of0,001 showed jointly between the Board of Commissioners and the Audit Committeeare effect on Quality of Financial Statement. This suggests the hypothesis 3 issupported. If the BOC rose by 1 then the quality of the Financial Statements (ROI)will go up 0159, but if the Audit Committee to rise by 1 it will not increase ROI.Adjusted R2 value of 0.142 which indicates the ability of the Board of Commissionersand the Audit Committee may explain the ROI of 14.20%, while the remaining85.80% is explained by other variables.